Four weeks of off-season training improves peak oxygen consumption in female field hockey players - Funch, L. T.; Lind, E.; True, L.; Van Langen, D.; Foley, J. T.; Hokanson, J. F. (Sports, 2017)
The purpose of the study was to examine the changes in peak oxygen consumption (VO2peak) and running economy (RE) following four-weeks of high intensity training and concurrent strength and conditioning during the off-season in collegiate female field hockey players. Fourteen female student-athletes (age 19.29 ± 0.91 years) were divided into two training groups, matched from baseline VO2peak: High Intensity Training (HITrun; n = 8) and High Intensity Interval Training (HIIT; n = 6). Participants completed 12 training sessions. HITrun consisted of 30 min of high-intensity running, while HIIT consisted of a series of whole-body high intensity Tabata-style intervals (75-85% of age predicted maximum heart rate) for a total of four minutes. In addition to the interval training, the off-season training included six resistance training sessions, three team practices, and concluded with a team scrimmage. VO2peak was measured pre- and post-training to determine the effectiveness of the training program. A two-way mixed (group × time) ANOVA showed a main effect of time with a statistically significant difference in VO2peak from pre- to post-testing, F(1, 12) = 12.657, p = 0.004, partial ?2 = 0.041. Average (±SD) VO2peak increased from 44.64 ± 3.74 to 47.35 ± 3.16 mL·kg-1·min-1 for HIIT group and increased from 45.39 ± 2.80 to 48.22 ± 2.42 mL·kg-1·min-1 for HITrun group. Given the similar improvement in aerobic power, coaches and training staff may find the time saving element of HIIT-type conditioning programs attractive